Transforming the Islamic Religious Education Curriculum through Digital Ethics in the Society 5.0 Era - Muhamad Ali; Mukhlis Akbar Absuhalini (Fakultas Ilmu Pendidikan Universitas Negeri Gorontalo, 2026)
This study aims to analyze the concept, transformation process, and implementation strategies of the Islamic Religious Education Curriculum based on digital ethics in responding to technological advancements in the Society 5.0 era. The study employed a qualitative approach using a library research design. Data were collected through documentation studies of books, scholarly articles, national and international journals, and policy documents relevant to the development of the Islamic Religious Education curriculum, digital ethics, and educational transformation. The data were analyzed using the content analysis technique through the stages of data reduction, categorization, interpretation, data presentation, and conclusion drawing. The findings reveal that the transformation of the Islamic Religious Education curriculum based on digital ethics is implemented through the innovation of learning outcomes, the development of contextual teaching materials, the application of technology-based learning strategies, the strengthening of digital literacy, and the integration of twenty-first-century competencies with Islamic moral values. Its implementation is reinforced through the development of a digital school culture, the enhancement of teachers' digital competencies, collaboration among schools, families, and communities, and authentic character assessment. This transformation contributes to developing students who are faithful, possess noble character, are digitally literate, demonstrate integrity, and act responsibly as digital citizens in the Society 5.0 era